Audit Tenure dan Ukuran Kantor Akuntan Publik Mempengaruhi Audit Delay - Ari Feryandi; Ely Suhayati (UNKLAB Business School, 2022)
Due to delays in annual financial reporting, a number of IDX issuers were subject to administrative sanctions by the Indonesia Stock Exchange. One of the reasons is that auditors find it difficult to confirm the financial statements of a company. This study seeks to ascertain how audit tenure and KAP size affect audit delay. Descriptive and verification methods with a quantitative approach were used in this study. 13 Public Accounting Firms in Bandung which are listed on the Indonesia Stock Exchange are the research samples. The research sample consisted of 40 auditors, with the sampling technique using Non Probability Sampling with Purposive Sampling. The analysis was performed using multiple linear regression. The test results of this study indicate that (1) audite tenure has an effect on audit delay with a strong and negative correlation and (2) the size of a public accounting firm has an effect on audit delay with a strong and negative correlation in public accounting firms in the city of Bandung which are listed on the stock exchange. Indonesia. Keywords: Audit Delay, Audit Tenure, Public Accounting Firm Size . administratif oleh BEI. Salah satu penyebabnya adalah auditor merasa kesulitan untuk mengkonfirmasi laporan keuangan suatu perusahaan. Penelitian ini berusaha untuk memastikan bagaimana Audit Tenure dan Ukuran KAP mempengaruhi Audit Delay. Metode deskriptif dan verifikatif dengan pendekatan kuantitatif digunakan dalam penelitian ini. 13 Kantor Akuntan Publik yang terdaftar di BEI yang berada di Kota Bandung menjadi sampel penelitian. Sampel penelitian terdiri dari 40 auditor, dengan teknik pengambilan sampel menggunakan Non Probability Sampling dengan Purposive Sampling. Analisis dilakukan dengan menggunakan regresi linier berganda. Hasil pengujian penelitian ini menunjukkan bahwa (1) Audite Tenure berpengaruh terhadap Audit Delay dengan korelasi yang kuat dan negatif dan (2) Ukuran KAP berpengaruh terhadap Audit Delay dengan korelasi kuat dan negatif pada KAP yang terdaftar di BEI yang berada di Kota Bandung yang terdaftar di Bursa Efek Indonesia. Kata kunci: Audit Tenure, Audit Delay, Ukuran Kantor Akuntan Publik.